SARS-CoV-2 omicron BA.5 and XBB variants have increased neurotropic potential over BA.1 in K18-hACE2 mice and human brain organoids - Stewart, Romal; Yan, Kexin; Ellis, Sevannah A.; Bishop, Cameron R.; Dumenil, Troy; Tang, Bing; Nguyen, Wilson; Larcher, Thibaut; Parry, Rhys; Sng, Julian De Jun; Khromykh, Alexander A.; Sullivan, Robert K. P.; et al. (Frontiers in Microbiology, 2023)
The reduced pathogenicity of the omicron BA.1 sub-lineage compared to earlier variants is well described, although whether such attenuation is retained for later variants like BA.5 and XBB remains controversial. We show that BA.5 and XBB isolates were significantly more pathogenic in K18-hACE2 mice than a BA.1 isolate, showing increased neurotropic potential, resulting in fulminant brain infection and mortality, similar to that seen for original ancestral isolates. BA.5 also infected human cortical brain organoids to a greater extent than the BA.1 and original ancestral isolates. In the brains of mice, neurons were the main target of infection, and in human organoids neuronal progenitor cells and immature neurons were infected. The results herein suggest that evolving omicron variants may have increasing neurotropic potential.